(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
A cross-sectional study was conducted at Kano Main Abattoir, Kano State, between November 2024 and February 2025 to evaluate the prevalence of indigestible substances in the rumen and reticulum of slaughtered small ruminants. The study examined 21,186 animals, comprising 5,488 sheep (ovine) and 15,698 goats (caprine), selected through a simple random sampling technique. During ante-mortem evaluation, data on gender, age, and body condition score (BCS) were recorded. Post-mortem examinations of the rumen and reticulum were performed to identify and document foreign materials in the gastrointestinal tracts. Out of the 3,828 animals examined, 300 (7.8%) were found to harbor various types of indigestible foreign materials. The prevalence was higher in sheep (8.1%) compared to goats (7.5%) (2=0.33, P>0.0001). Adult animals exhibited a significantly higher prevalence (12.8%) than younger ones (4.04%) (P<0.0001; 2=51.4; OR=0.29). No significant difference was observed between males (6.7%) and females (8.1%) (P>0.0001; 2=0.74; OR=0.82). Animals with poor BCS showed a higher prevalence compared to those with medium or good BCS. The study revealed that indigestible foreign materials were more frequently recovered from the rumen than the reticulum in both sheep and goats. Polythene bags (66.7%) were the most commonly encountered foreign material, followed by clothing items (24.3%), mosquito nets (6.7%), hair (2%), and nails (0.3%). Predisposing factors included inadequate plastic waste disposal systems, poor livestock management practices, and free grazing. To address these issues, collaborative intervention schemes involving government agencies and livestock farmers are recommended to raise public awareness about proper domestic waste disposal practices.